Integration of Campus Culture Towards Islamic Character Values in Elementary Social Science Learning - Desy, Desy Anindia Rosyida; Suyitno; Chosinawarotin; Erdawati (Tarbawi, 2023)
Campus culture has a big influence on the formation of a student's character. As a student studying on an Islamic campus, you definitely have to have an Islamic character. The Islamic character formed from campus culture will reflect a student's personality, both in daily life and in the teaching and learning process. Character formation is very important to instill, especially in prospective elementary school teacher students. This is done through teaching activities in elementary school social studies learning. Elementary social studies is a subject that teaches how to interact with others. To provide good student interactions, good character is also needed, especially the Islamic character of students who will later become output from Balitar Islamic University. The research method used is descriptive qualitative. The results obtained from direct observations in the field show that campus culture is related to the formation of Islamic character through elementary social studies learning. The campus culture includes: dhikr and prayers every Friday morning, Ramadan festivals, covering the intimate parts, saying hello, praying before and after studying.